The Mechanism of Human Connectedness in Relationship to Physical Health, Mental Health, and Cognitive Function Among the Elderly in Rural China - Xu, Shicun; Wang, Yuanyuan; Yu, Hui (Frontiers in Psychiatry, 2021)
Background: Elderly people face particular challenges in their everyday lives, and these are likely to be caused by physical health, mental health, cognitive function, and lack of maintaining a connection to other people. This study aims to explore a meaningful measure of human connectedness among the elderly in rural China and to examine the extent to which it impacts elderly people's physical and mental health as well as their cognitive function. Methods: Survey data were collected from 483 participants who were aged 60 and older in northeast rural China. The outcome variables included cognitive function, which was assessed by the Short Portable Mental Status Questionnaire; depressive symptoms, which were measured by the 10-item version of the Center for Epidemiologic Studies Depression Scale; and the participants' physical health, which was assessed by a 15-item checklist. On the other hand, human connectedness was constructed by perceived family support, which was measured by the Multidimensional Scale of Perceived Social Support; the sense of community, which was measured by the Brief Sense of Community Scale; and the satisfaction of connectedness with others (i.e., with family members and friends). Results: Structural equation modeling analysis confirms that perceived family support, community feelings, and perceived satisfactory connections with family and friends constitute a sufficient representation of human connectedness. Moreover, human connectedness also significantly predicted one's mental and physical well-being as well as cognitive function (b = 0.11, SD = 0.02, β = 0.50, p < 0.001; model fitting indexes X(16)2 = 17.27, p = 0.368, CFI = 0.998, and RMSEA = 0.013). Conclusion: The present study is the first attempt to explore the latent structure of human connectedness and its positive impact on cognitive function as well as physical and mental health among elderly people. The implications and the importance of fostering a stronger social support network, especially for the aging population, are discussed.